Analisis Money Management terhadap Kondisi Keuangan Mahasiswa Rantau - Jannah, Annisa I’zzatul; Amalia, Diah; Marischa, Naifa Nur; Azyan, Nayla Ikhsani; Afriyanti, Nur Afipah; Ningati, Restu Setia; Rozak, Rama Wijaya Abdul (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to find out how the financial condition of overseas students is in managing their finances independently. This research uses a descriptive quantitative method by distributing a digital questionnaire in the form of a Google Form which is shared on social media. This research was conducted on overseas students in Indonesia based on class, gender, region of origin, and monthly pocket money, as well as the influence of lifestyle on their financial management. The results of this research show that women have better financial management compared to men in their daily lives. The pocket money that overseas students receive every month also influences their financial management. The application of money management in everyday life is very important for overseas students. Therefore, researchers provide effective ways regarding how to manage finances well.